2018
DOI: 10.3390/cryst8020090
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Hydride Composite of Mg2NiH4 with Borohydrides Eutectic Mixtures

Abstract: Abstract:The development of materials showing hydrogen sorption reactions close to room temperature and ambient pressure will promote the use of hydrogen as energy carrier for mobile and stationary large-scale applications. In the present study, in order to reduce the thermodynamic stability of MgH 2 , Ni has been added to form Mg 2 NiH 4 , which has been mixed with various borohydrides to further tune hydrogen release reactions. De-hydrogenation/re-hydrogenation properties of Mg 2 NiH 4 -LiBH 4 -M(BH 4 ) x (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…For instance, the occurrence of a liquid phase enable easy tailoring of the decomposition temperature of borohydrides by both nanoconfinement, and in mixture with reactive hydride composites ,. The presence of a liquid phase in reactive hydride composites, provides a synergic effect in improving hydrogen release and cyclability ,. Improvements in hydrogen release properties in these systems are usually related to interfaces and microstructures, where the liquid phase promotes local contact between boundaries of the complex hydrides in the mixture .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the occurrence of a liquid phase enable easy tailoring of the decomposition temperature of borohydrides by both nanoconfinement, and in mixture with reactive hydride composites ,. The presence of a liquid phase in reactive hydride composites, provides a synergic effect in improving hydrogen release and cyclability ,. Improvements in hydrogen release properties in these systems are usually related to interfaces and microstructures, where the liquid phase promotes local contact between boundaries of the complex hydrides in the mixture .…”
Section: Introductionmentioning
confidence: 99%
“…The latter species are boron donors to reversibly form the borohydride during the re-hydrogenation process. Dematteis et al [191] also observed a lower decomposition temperature of the RHC mixture if LiBH 4 is in a eutectic mixture with borohydrides that contain stable single charged metal cation, while a leftover of the more stable borohydrides was detected after cycling. In the eutectic mixture, the presence of double charged metal cation (i.e., Ca(BH 4 ) 2 and Mg(BH 4 ) 2 ) leads to a complete decomposition of the borohydrides.…”
Section: Hydrogen Sorage Properties Of Eutectic Metal Borohydride Systemsmentioning
confidence: 91%
“…It has been evidenced that composite systems containing lithium borohydride (LiBH 4 ) [190], or mixture of borohydrides, or borohydrides and reactive hydride composites, have improved hydrogen storage properties, especially when a liquid phase is involved [191]. Furthermore, variating composition and crystal structure can lead to a fine-tuning of kinetics and thermodynamics of hydrogen storage properties as a function of temperature, pressure and phase stability.…”
Section: Libh 4 -Linhmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixtures of borohydrides may have an easier release of hydrogen than that of the individual constituents. In fact, the formation of solid solutions can lead to a lowering of the decomposition temperatures and a change of reaction mechanisms [19][20][21]. According to the Density Functional Theory (DFT) calculations of Ozolins et al [2], mixtures of Mg(BH 4 ) 2 and Ca(BH 4 ) 2 have better thermodynamic properties with respect to pure components.…”
Section: Introductionmentioning
confidence: 99%